The Impact Of Excessive Use Of Social Media On Mental Health Among Youth In Uzbekistan - Abdiazimov Samandar Islom o’gli; Allamurodov Ergash Abduraxmat ogli; Zairov Akmaljon Zakir o'g'li; Nasriddinova Shaxnoza Musurmon qizi (Open Academia, 2025)
This article analyzes the impact of excessive use of social networks on mental health among Uzbek youth. The article provides information on the impact of social networks on the reward system of the human brain, the effect of dopamine release on mental state, and the increase in conditions such as stress, anxiety, and depression. The study highlights the main psychological problems observed among Uzbek youth - decreased motivation, inability to concentrate, and low self-esteem. The article also analyzes the medical and psychological aspects of these conditions and provides effective recommendations for maintaining mental health using social networks.
Keywords: social networks; mental health; youth psychology